Inner selfie: Photography as an aesthetic experience of recognition - De Barros, Laan Mendes [UNESP]; De Castro, Rodrigo Galvão [UNESP] (Colegio Mayor de Nuestra Senora del Rosario, 2020)
This study described and discussed an aesthetic experience in which photographic images are initially understood from the perspective of mediating the relationships of one’s self with the world, in how we see ourselves, and how we also see ourselves in the other and by the other. It was based on a project called “Indoor Selfie,” conducted with a group of university students invited to create prospective representations of themselves not through their own image but through a viewpoint based on what they see themselves represented in. This project included awareness-raising practices and studied photography, from which this work sought to understand how identity construction occurs in media society, in increasingly intense relationships of interaction between human beings and information and communication technology devices. The methodology used included a reflection on the “indoor selfie” concept from a bibliographic review that brought up ideas such as “media bios” (Sodré, 2002), “society in media coverage” (Braga, 2006), and “post-photography” (Fontcuberta, 2016) and discussed the “act of seeing” (Didi-Huberman, 2010) and the “act of photographing” (Sontag, 2004). It was observed that the works produced by the students, and described in the study, are intense aesthetic experiences wherein relations of alterity appear through photography as a device for self-recognition and recognition of one’s self that exists in the other.
Selfie interior: La fotografía como experiencia estética de reconocimiento
Selfie interior: A fotografia como experiência estética de reconhecimento
Keywords: Aesthetic experience; Image and recognition; Inner selfie; Photography